Implementasi Sistem Informasi Web untuk Visualisasi dan Keamanan Data Susut Energi - Jati Nur Shiddiq (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The advancement of information technology has encouraged organizations to transform their data management practices, including those within the electrical power sector. PT PLN (Persero) UP3 Lubuk Pakam previously utilized Google Sheets to store and manage electrical energy loss data. However, this approach posed data security risks, as the files could be accessed and modified by unauthorized individuals. To overcome these limitations, this study developed a web-based information system specifically designed for the Electricity Energy Transaction Division (TEL) to replace Google Sheets as a platform for managing energy loss data. The proposed web application integrates a Role-Based Access Control (RBAC) mechanism, ensuring that only administrators are authorized to input, edit, or delete data, while other users can only view validated records. Furthermore, the system incorporates interactive data visualization through real-time charts, facilitating effective monitoring and analysis of electrical energy losses. The implementation of this system is expected to enhance data security, accuracy, and management efficiency within the TEL Division of PT PLN UP3 Lubuk Pakam.